Ultra-brief training in cognitive reappraisal or mindfulness reduces anxiety and improves motor performance efficiency under stress - Wolfe, Emma C.; Thompson, Andrew G.; Brunyé, Tad T.; Caroline Davis, F.; Grover, Daniel; Haga, Zachary; Doyle, Thomas; Goyal, Anjali; Shaich, Hannah; Urry, Heather L. (Anxiety, stress, and coping, 2023)
We examined the effects of ultra-brief training in mindfulness and cognitive reappraisal on affective response and performance under stress. We hypothesized that one or both types of training would decrease affective responding and improve performance, and that these effects might be moderated by acute stress induction. We manipulated training (mindfulness, cognitive reappraisal, control) between subjects and level of stress (low, high) within subjects in a 3 × 2 mixed factorial design. Method: Participants (N = 112, ages 18-35) completed two sessions on different days. In each session, they received mindfulness or cognitive reappraisal training or listened to a control script prior to a low- or high-stress simulated hostage situation. We measured motor performance efficiency (proportion of shots that hit hostile and hostage targets), affective responding (self-reported anxiety, salivary cortisol and alpha amylase, and autonomic physiology), and physical activity. Compared to control instructions, ultra-brief training in cognitive reappraisal or mindfulness reduced subjective anxiety and increased performance efficiency. There were few effects of training on other measures. Ultra-brief training in cognitive reappraisal or mindfulness prior to a stressful task may be both helpful and harmful; effects are preliminary and subject to boundary conditions.